The Effect of Contact Lens Wearing Time on Corneal Health: An Optometry Perspective - Sari, Dian Leila; Livanos, Fetrix; Shoviana, Nuria (Universitas Ibn Khaldun Bogor, 2025)
The use of contact lenses has become a popular choice for vision correction. However, excessive duration of contact lens wear can affect corneal health and increase the risk of eye complications. This study aims to analyze the effect of contact lens wearing time on corneal health, especially in daily and monthly contact lens users. This research method is a descriptive-analytical study involving 37 respondents who use contact lenses with variations in the duration of use, ranging from 4 to 12 hours per day who have refractive errors and keratometer values (a tool used to measure the curvature of the front surface of the cornea) in the range H range 7.350 mm – 8.25 V 7.10 – 8.10 mm. Data were collected through eye examination using a slit-lamp and measurement of hydration and corneal oxygenation. The moisture content of contact lenses is how much water is in the lens. The higher the moisture content in the contact lenses, the more oxygen reaches the cornea during the wearing of the contact lenses. This study aims to examine the effect of contact lens wearing time on the patient's corneal health, especially from an optometry perspective. The results showed that wearing contact lenses for more than 8 hours per day was significantly correlated with increased symptoms of eye irritation, decreased corneal hydration, and decreased oxygen permeability, potentially leading to complications such as keratitis and dry eye syndrome. The conclusion of this study emphasizes the importance of limiting the time of wearing contact lenses and regular monitoring of eye health for contact lens users to prevent serious complications of the cornea.